The history of the Department of Christian Education of the executive council of the Episcopal Church : 1958-1968 - McElligot, Ann Elizabeth Proctor ([New York] : General Theological Seminary, 1984)
"Throughout the 1950's, educational issues and the work of the Department of Christian Education occupied a key position in the concerns of the Church as represented by the program requests of General Convention, the attention of its interim deliberative body, the National Council (now known as the Executive Council), and the proportion of the annual budget is commanded. In response to the program requests of the 1950s, the Department organized itself to most efficiently produce a curriculum and prepare the Church to use it effectively..."- Introd.
Submitted in partial fulfillment of the requirements of the degree of Master in Divinity
Thesis (M.Div.) -General Theological Seminary, New York City